10.30999 Edukasi Kesehatan: Cegah Anemia Pada Remaja Putri di SMA Negeri 1 Cimalaka - Laeli Chaerina; Haq, M. Iqbal Arinal; Aidah, Dila Nur; Amelia Rifandini; Sakinah, Hajar Zulva; Suryani, Anggi Nabilla; Rahmat, Delli Yuliana (LPPM UNINUS, 2024)
The prevalence of anemia in Sumedang Regency is quite large with 2,485 thousand (20.6%) out of 12,064,15 people (Sumedang Regency Health Service, 2023). Cimalaka sub district is in the 3rd largest position in Sumedang with the results of 402 teenagers experiencing anemia out of 907 teenagers screened or around 44.32% of those screened. This research method uses a quantitative type of research with a Pre-Experimental research design with a one group pre-post test design on 72 female students aged 15-16 years at one of the high schools in Sumedang Regency. The results of statistical tests using the Paired Sample T Test show a significance value (2-tailed) of 0.000 which indicates confidence at a 95% interval. The conclusion of this research is that providing health education about anemia has proven to be effective with an increase in the average value of students' total knowledge before health education to 63.75 and after health education to 74.44.